Editorial Board and Table of Contents - Sausverde, Ērika; Steponavičiūtė, Ieva (Scandinavistica Vilnensis, 2009)
In autumn 2007, the Centre of Scandinavian Studies at Vilnius University hosted an international conference on Old Norse literature, mythology, culture, social life and language, held on the occasion of the 200th anniversary of the publication in Vilnius of Edda Skandinawska by Joachim Lelewel. The title of the conference − Dialogues with the Viking Age − was borrowed from the book by Vésteinn Ólason, with the author’s kind consent. The conference became a momentous event in the history of the Centre, as it gathered together many of our good friends from throughout the years: Professors Thomas Bredsdorff (Denmark), Jan Ragnar Hagland and Jon Gunnar Jørgensen (Norway), Jurij K. Kusmenko (Russia and Germany), Vésteinn Ólason (Iceland), Dr. Kristel Zilmer (Estonia) and Dr. Aurelijus Vijūnas (Taiwan). Although, for obvious reasons titled differently, the present book consists of the proceedings of that conference almost in their entirety, as well as a couple of extra articles by those authors who were not able to come to Lithuania at that time. We are grateful to all contributors, reviewers and sponsors who made it possible for the conference to take place and for the book to appear. Special thanks go to Ugnius Mikučionis and Dr. Aurelijus Vijūnas for their generous help in, respectively, organising the conference and editing the book.
Keywords: none